Integrating Quizizz In Learning: Can It Strengthen Elementary School Students' Learning Motivation? - Haris, Astrifa Nadia; Krismanto, Wawan; Shasliani, Shasliani (Pedagogik Journal of Islamic Elementary School, 2024)
Previous research has studied using Quiziz, but only for learning assessment. To make the literature more diverse, this research examines the integration of Quizizz into complete learning, starting from opening learning activities, delivering material, discussion activities, and learning assessments. In addition, the research aims to compare the motivation of students whose learning integrates Quizizz with conventional learning. The method used is quantitative, with a type of quasi-experimental research in the form of a post-test-only control design. The population in this study was 268 students. In comparison, the sample was class 5A as an experimental class with 21 students and class 5B as a control class with 23 students. The treatment given in the experimental class is to integrate Quizizz into the learning process. A learning motivation questionnaire obtained research data. The results of the Independent Sample T-Test test show Sig. (2-tailed) 0.000 < 0.05 means that there is a difference between the learning motivation of students whose learning integrates Quizizz and those whose learning uses conventional learning. Students in classes whose learning integrated Quizizz showed better learning motivation than those with conventional learning in class 5 UPT SD Negeri 5 Amparia Sidrap, South Sulawesi.